A transition from using multi‐step procedures to a fully integrated system for performing extracorporeal photopheresis: A comparison of costs and efficiencies. Issue 6 (17th April 2017) - Azar, Nabih; Leblond, Veronique; Ouzegdouh, Maya; Button, Paul
Abstract: Introduction: The Pitié Salpêtrière Hospital Hemobiotherapy Department, Paris, France, has been providing extracorporeal photopheresis (ECP) since November 2011, and started using the Therakos ® CELLEX ® fully integrated system in 2012. This report summarizes our single‐center experience of transitioning from the use of multi‐step ECP procedures to the fully integrated ECP system, considering the capacity and cost implications. Materials and Methods: The total number of ECP procedures performed 2011–2015 was derived from department records. The time taken to complete a single ECP treatment using a multi‐step technique and the fully integrated system at our department was assessed. Resource costs (2014€) were obtained for materials and calculated for personnel time required. Time‐driven activity‐based costing methods were applied to provide a cost comparison. Results: The number of ECP treatments per year increased from 225 (2012) to 727 (2015). The single multi‐step procedure took 270 min compared to 120 min for the fully integrated system. The total calculated per‐session cost of performing ECP using the multi‐step procedure was greater than with the CELLEX ® system (€1, 429.37 and €1, 264.70 per treatment, respectively). Conclusions: For hospitals considering a transition from multi‐step procedures to fully integrated methods for ECP where cost may be a barrier, time‐driven activity‐based costing should be utilized to gain a more comprehensive understanding the full benefit that such a transition offers. The example from our department confirmed that there were not just cost and time savings, but that the time efficiencies gained with CELLEX ® allow for more patient treatments per year.